Immune Checkpoint Inhibitors in Hepatocellular Cancer: Current Understanding on Mechanisms of Resistance and Biomarkers of Response to Treatment - Onuma, Amblessed E. (Gene Expr, 2020)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy worldwide and a leading cause of death worldwide. Its incidence continues to increase in the US due to hepatitis C infection and nonalcoholic steatohepatitis. Liver transplantation and resection remain the best therapeutic options for cure, but these are limited by the shortage of available organs for transplantation, diagnosis at advanced stage, and underlying chronic liver disease found in most patients with HCC. Immune checkpoint inhibitors (ICIs) have been shown to be an evolving novel treatment option in certain advanced solid tumors and have been recently approved for inoperable, advanced, and metastatic HCC. Unfortunately, a large cohort of patients with HCC fail to respond to immunotherapy. In this review, we discuss the ICIs currently approved for HCC treatment and their various mechanisms of action. We will highlight current understanding of mechanism of resistance and limitations to ICIs. Finally, we will describe emerging biomarkers of response to ICIs and address future direction on overcoming resistance to immune checkpoint therapy.